Downfall of pollen carriage by ants after Argentine ant invasion in two Mediterranean Euphorbia species - Blancafort, X.; Gómez, C. (VIE ET MILIEU-LIFE AND ENVIRONMENT, 2006)
We have studied the influence of Argentine ant invasion on the level of pollen grain carriage by ants in Euphorbia characias and E. biumbellata, two deciduous shrubs visited by ants. The observations were made in two contiguous areas, invaded and non-invaded by the Argentine ant Linepithema humile, in a Mediterranean cork-oak forest. In the invaded area L. humile displaced all native ants that climb to the cyathia of the inflorescences, except Plagiolepis pygmaea, a tiny ant species. Eight native ant species were detected in non-invaded areas. Camponotus cruentatus (52.06 +/- 5.57 pollen grains carried per ant worker of E. characias and 38.84 +/- 6.82 pollen grains of E. biumbellata, mean se) and Camponotus piceus (42.80 +/- 21.57 pollen grains of E. biumbellata) carried much more pollen than L. humile worker ants (0.37 +/- 0.06 pollen grains of E. characias and 0.44 +/- 0.21 pollen grains of E. biumbellata). The Argentine ant and the native ants collected nectar, but C. cruentatus, the visiting ant species most abundant in the non-invaded area, touched the anthers or the stigma of the flowers three times more frequently than the Argentine ant. These results suggest the Argentine ant displace the native ants and that the invasion could interfere with natural visitors or potential pollinators in several plants.
The following values have no corresponding Zotero field: pub-location: LABORATOIRE ARAGO, BP 44, 66651 BANYULS-SUR-MER CEDEX, FRANCE publisher: OBSERVATOIRE OCEANOLOGIQUE BANYULS
Keywords: Biological invasion; pollen carriage; pollination